A Needs Assessment for Type 2 Diabetes Prevention at a Community Food Bank in British Columbia, Canada - Jenna A. P. Sim; Sarah A. Craven; Kaela D. Cranston; Trevor R. Moss; Mary E. Jung (Health Promotion Practice, 2026)
People experiencing food insecurity experience higher rates of type 2 diabetes (T2D) than those who are food secure. Small Steps for Big Changes (SSBC) is a T2D prevention program in Kelowna, British Columbia, Canada. This study aimed to learn the factors that influenced people experiencing food insecurity in the community’s ability to engage in T2D prevention behaviors, participate in SSBC, and the food bank’s ability to provide T2D prevention services to their users. Focus groups were held with food bank users and interviews with food bank employees to learn these factors. The focus groups and interviews were analyzed using reflexive thematic analysis followed by deductive barrier and facilitator coding to the theoretical domains framework (TDF). Three themes were constructed from the focus groups with food bank users: (a) Using the Food Bank: Pulled in Two Directions, (b) Knowledge is Both Opportunity and Responsibility, and (c) Competing Priorities. Two themes were constructed from interviews with food bank employees: (a) A Dream: The Desire to Help in All Aspects of Wellbeing and (b) The Reality: Under Pressure. The most prominent TDF barrier to engaging in SSBC was knowledge, and the most prominent barrier to T2D prevention behaviors was environmental context and resources. The most prominent TDF barrier to delivering T2D services was environmental context and resources. Results of this study highlight the complexities of T2D prevention while experiencing food insecurity and provide insights for how SSBC and other T2D prevention programs can support people experiencing food insecurity.